Stategi Guru PAI dalam Menumbuhkan Budaya Religius Kelas XI 2 di SMAN 1 Palangka Raya - Andhika Nirwan Arief; Ajahari Ajahari; Aghnaita Aghnaita (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the strategies used by Islamic Education (PAI) teachers in fostering a religious culture in class XI-2 at SMAN 1 Palangka Raya. The background to this study is the increasing moral degradation among teenagers due to the massive negative influence of social media, resulting in a lack of spiritual character building in public schools. As a preventive measure, the school has attempted to take steps to foster a religious culture. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The subjects of this study include: 2 PAI teachers, and the informant: the school principal. The research findings indicate that the PAI teachers' strategies include fostering religious activities, teacher role modeling, integrating religious values into learning, and collaborating with parents. These strategies have proven to enhance religious participation and strengthen students' spiritual character. Challenges faced include limited mosque facilities and the influence of digital media, but these can be addressed through digital innovation and educational institution support. This study recommends strengthening school-parent collaboration, enhancing teacher capacity, and developing worship monitoring technology to support the effectiveness of religious education in public schools.